An enhanced approach for damage detection using the electromechanical impedance with temperature effects compensation - Dias, Lorena Lopes [UNESP]; Lopes, Kayc Wayhs [UNESP]; Bueno, Douglas D. [UNESP]; Gonsalez-Bueno, Camila Gianini [UNESP] (Springer Nature, 2023)
Damage detection is one of the great challenges of the maintenance tasks and it has involved numerous researches to develop techniques in the field of structural health monitoring (SHM). Among different techniques, electromechanical impedance (EMI) technique has attracted attention due to its important and promising results. However, the sensitivity of this technique to variations in environmental conditions can lead to false diagnoses, and the temperature is one of the most critical factors for EMI technique. In view of this point, different researchers have developed compensation techniques to minimize the effects caused by temperature variation in electromechanical impedance measurements. Another important issue related to electromechanical Impedance curves is about the frequency range chosen to be analyzed. Then, the present article introduces an improved approach for damage detection by adding a new step for the temperature compensation technique proposed in a well-established approach in the literature. The proposal comprises a strategy to select the frequency range to compute damage detection indexes, and the technique is demonstrated for an aluminum beam in three different structural conditions: corresponding to the healthy and two types of damaged structure. The results are investigated for four different frequency ranges. The findings demonstrate the effectiveness of the proposed approach to reduce false alarms in damage detection using the EMI technique.
Keywords: Electromechanical impedance; Experimental data; Structural health monitoring; Temperature compensation technique; Temperature effects